Outside in, Inside Out: Tourism Competitiveness and Brazilian Strategy Analysis - Mazaro, Rosana (Journal of Tourism Management Research, 2019)
The paper identifies and characterizes the Brazilian strategy to cope with the international competitiveness in tourism as well as implementation of the governance mechanisms suitable for regions and destination in the country. This research is a case study using qualitative analysis and descriptive results. Investigative procedures adopted the methods of the documents content analysis and specialised bibliography. It is used the T&TCI-WEF series secondary data sources for analysis “Outside In” and the ICTN-MTUR for “Inside Out” analysis. The comparison between both shows symmetrical similarity between the results and distinct point of the view are converging and similar in the overall analysis of Brazil destination’s competitiveness. Infrastructure, safety and security problems and unstable business environment are factors, which burden further T&T development in the country. From the point of view of opportunities, the analysis of the evolution of both views reveals and highlights important elements for the establishment of tourism competitiveness strategies for Brazil in base its potential.